Coupling Ion Specificity of the Flagellar Stator Proteins MotA1/MotB1 of Paenibacillus sp. TCA20 - Sakura Onoe; Myu Yoshida; Naoya Terahara; Yoshiyuki Sowa (Biomolecules, 2020)
The bacterial flagellar motor is a reversible rotary molecular nanomachine, which couples ion flux across the cytoplasmic membrane to torque generation. It comprises a rotor and multiple stator complexes, and each stator complex functions as an ion channel and determines the ion specificity of the motor. Although coupling ions for the motor rotation were presumed to be only monovalent cations, such as H+ and Na+, the stator complex MotA1/MotB1 of Paenibacillus sp. TCA20 (MotA1TCA/MotB1TCA) was reported to use divalent cations as coupling ions, such as Ca2+ and Mg2+. In this study, we initially aimed to measure the motor torque generated by MotA1TCA/MotB1TCA under the control of divalent cation motive force; however, we identified that the coupling ion of MotA1TCAMotB1TCA is very likely to be a monovalent ion. We engineered a series of functional chimeric stator proteins between MotB1TCA and Escherichia coli MotB. E. coli ΔmotAB cells expressing MotA1TCA and the chimeric MotB presented significant motility in the absence of divalent cations. Moreover, we confirmed that MotA1TCA/MotB1TCA in Bacillus subtilis ΔmotABΔmotPS cells generates torque without divalent cations. Based on two independent experimental results, we conclude that the MotA1TCA/MotB1TCA complex directly converts the energy released from monovalent cation flux to motor rotation.